Quantum chemical study of proton transfer mechanism of hydrated single and double propyl sulfonic acid [electronic resource] - Syarah Mat Udin, 1988- (2013)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2013